Application of Powerpoint Hyperlinks to Students' Interest in Learning Football Passing in Class VI - Ghiffari, Twiska Naufal Arsyah; Andrijanto, Doni; Johanis, Feri (Champions: Education Journal of Sport, Health, and Recreation, 2025)
This research aims to increase students' interest in learning football passing by using Powerpoint Hyperlink. This research uses a classroom action research method with 2 cycles using questionnaires to obtain data. In each cycle there is planning, implementation, observation and reflection. In cycle I, a pretest was carried out and in cycle II, treatment and post-test were carried out. The sample for this research used 32 students in class VI B at SDN Gading 1 Surabaya. The results of research conducted in cycle I showed that 3 students had a very high level of interest in learning, 4 students had a high level of interest in learning, 15 students had a medium level of interest in learning, and 10 students had a low level of interest in learning. In the implementation of cycle II, data was obtained that 11 students had a very high level of interest in learning, 6 students had a high level of interest in learning, 11 students had a moderate level of interest in learning, and 4 students had a low level of interest in learning. Thus, the average student score from cycle I was 85.87 and cycle II was 93.27 and showed an increase in student interest in learning by 8.4%. So a conclusion can be drawn if from the average score and completeness of the results students' interest in learning has increased after being given Power Point Hyperlink media with football passing material so that the learning strategy can be said to be effective.